Different Effects of Cold Stimulation on Reflex and Non-Reflex Components of Poststroke Spastic Hypertonia - Li, Sheng; Shin, Henry; Zhou, Ping; Li, Xiaoyan (Frontiers in Neurology, 2017)
Objective To use an established biomechanical approach to quantify reflex and non-reflex responses from spastic–paretic elbow flexors in response to controlled cold and heat stimulation. Methods Thirteen spastic–hemiplegic stroke subjects were tested in the experiment. The spastic elbow joint was stretched into extension for 50° at two speeds (5°/s and 100°/s) in a customized apparatus. Thermal stimulation (HEAT at heat pain threshold, COLD at 0°C, or BASELINE at room temperature) was applied to the thenar eminence of the contralateral hand immediately prior to stretching for at least 30 s. Results Total torque was greater at 100°/s than at 5°/s. Total torque was significantly increased after COLD, but not HEAT as compared to BASELINE. When normalized to total torque at baseline, HEAT decreased total torque by 6.3%, while COLD increased total torque by 11.0%. There was no significant difference in the reflex torque among three thermal conditions. Conclusion The findings demonstrate differentiated effects of cold stimulation on the total resistance from spastic muscles. They provide objective evidence for anecdotal clinical observations of increased muscle spasticity by cold exposure.